The Tao of computing - Walker, Henry M. (Chapman & Hall/CRC textbooks in computing., 2013)
Underlying Building-Block QuestionsHow Are Computers Organized?How Are Numbers and Characters Represented in a Computer (and Who Cares)?How Are Images Represented (and Does It Matter)?Where are Programs and Data Stored?What is an Operating System and What Does It Do?Software/Problem-Solving QuestionsWhat Can Computers Do for Me?What Should I Know about the Sizes and Speeds of Computers?How Are Software Packages Developed?Networking/Distributed System QuestionsHow Are Computers Connected?How Do Computers Share Information, So That I Can Exchange Materials with Others Using a Computer Network?Wh.